AGN dusty plasma polarization features. Issue Volume 10:Issue S313(2014) (24th March 2015) - Lopez, Ericson D.; Deustua, Susana
Abstract: We present the results of a theoretical study on the influence of dust particles on the polarization properties of the radiation that propagates along the jet in AGNs. First, a model for describing the interaction of dust particles, in addition to the electrons and ions, with electromagnetic radiation in a magneto-active plasma has been developed. From here, the contribution of dust particles to the Faraday rotation of the plane of polarization of the electric vector can be deduced. This model is evaluated for the outer region of the jet where the presence of dust particles are assumed, the magnetic field is weak and the electron density is low. Our results show that the dust particles give a significant contribution to the linear Faraday rotation measure.